Native and Non-Native Listeners Perceptual Judgement of English Accentedness, Intelligibility, and Acceptability of Indonesian Speakers - Zahro, Syifa' Khuriyatuz (Lingua Cultura, 2019)
This research aimed at investigating the extent of accentedness and intelligibility as well as the acceptability of Indonesian foreign-accented speech perceived by native and non-native listeners, as well as finding their correlation to each other. It used qualitative research. The participant of the research was selected using purposive sampling. The participants were divided into speakers and listeners. There are six speakers and four listeners selected. The four listeners were native and nonnative listeners who rated and transcribed six recorded reading of Indonesian speakers by means of SPIN (Speech Perception in Noise) test. The results show that native listeners rate the speech almost the same way as non-native listeners do. The speeches with clear and accurate pronunciation are rated highly accepted and fully intelligible, regardless of having a very strong accent. In contrast, less clear and accurate pronunciations, as well as a very strong accent of the speeches, are rated unacceptable and still reasonably intelligible. The result of the correlation test between accentedness and intelligibility as well as accentedness and acceptability of the accent finds on no account of correlation to each other. Therefore, accentedness and intelligibility plus accentedness and acceptability of the accent are independent, so that strong foreign accent could stay acceptable and intelligible. The factors found to influence the judgment are the familiarity of the accent, clarity, and accuracy of pronunciation. Aforementioned findings have implication to challenge English teachers in Indonesia to develop meaningful activities to teach English pronunciation accurately to be regarded as fully intelligible and acceptable by listeners, especially native English listeners.